PELATIHAN PEMANFAATAN PERANGKAT LUNAK (MICROSOFT OFFICE WORD, EXCEL, POWER POINT) DALAM KINERJA PENGOLAHAN DATA DI PEMERINTAHAN DESA BAGIKEPALA DESA SE-KECAMATAN BATANG ANGKOLA - Sormin, Masdelima Azizah; Sahara, Nur; Agustina, Lisna (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2018)
IbM discusses the utilization of software in assisting the village head Performance SeiBatangAngkola. His goal was to provide the skills and ability in using the device and take advantage of information and communication technology priority needs, improving basic capabilities in solving problems that will be faced in life in the village environment, enhancing the knowledge of computer-based administrative system, improve the skills of operating computer devices to improve the documentation of the data. The next performance is measured through the ability to process and use the software in question. Respondents who used as many as ten people on the research of the village chief in the village BatangAngkola. This dedication was held in Balai Village PurbaNauliBatangAngkola. The method of implementation is done in the form of training. Public service was conducted for three months, in January-March 2016. Where the activities of the training were held for two days in a row. The results of the training software arethat the head of the village is already a lot of information and motivation so that in general the village chief has been able to operate your laptop or computer.External training activities resulting from this software is a journal with ISSN and servicesfrom training activities undertaken then expected to provide information, knowledge and can help the village chief in typing the letters to complete the administration of the village.Â Key words:Software, The Performance Of The Village Chief, A Batang Village Of Angkola